Financial Reporting, Financial Statement Analysis, and Valuation / A Strategic Perspective: Sixth Edition - Brown Paul R; Stickney Clyde P; Wahlen James M (Thomson, 2007)
This book provides students with resources that demonstrate the applications of financial analysis. Preface, Overview of Financial Reporting and Financial Statement Analysis and Valuation, Asset and Liability Valuation and Income Measurement, Income Flows Versus Cash Flows: Key Relationships in the Dynamics of a Business, Profitability Analysis, Risk Analysis, Quality of Accounting Information and Adjustments to Reported Financial Statement Data, Revenue Recognition and Related Expenses, Liability Recognition and Related Expenses, Intercorporate Entities, Forecasting Financial Statements, Risk-Adjusted Expected Rates of Return and the Dividends Valuation Approach, Valuation: Cash-Flow-Based Approaches, Valuation: Earnings-Based Approaches, Valuation: Market-Based Approaches, Financial Statements and Notes for PepsiCo Inc. and Subsidiaries, Management's Discussion and Analysis for PepsiCo Inc. and Subsidiaries, Financial Statement Analysis Package (FSAP), User Manual for Financial Statement Analysis Package (FSAP), Index.